A new cheirolepidiaceae (Coniferales) from the early jurassic of patagonia (argentina): Reconciling the records of impression and permineralized fossils - Escapa, Ignacio Hernán (2017)
PREMISE OF THE STUDY: Plants preserved in different fossil modes provide complementary data concerning the paleobiology and evolutionary relationships among plant groups. New material from the Early Jurassic of Patagonia shows the importance of combining these sources of information, as we describe the first compression/impression fossils of Pararaucaria, a genus of the extinct conifer family Cheirolepidiaceae previously known from permineralized fossils. These fossils extend the temporal range of this genus and may allow its wider recognition in the fossil record. METHODS: We studied fossil plants from the Early Jurassic (Pleinsbachian-Toarcian) locality of Taquetrén in Patagonia, Argentina using standard paleobo-tanical preparation and description techniques. KEY RESULTS: Pararaucaria taquetrensis consists of isolated ovuliferous scales and small seed cones with helically arranged bract-scale complexes attached to scale-leaf foliage. Bract-scale complexes consist of separated bracts and ovuliferous scales with two seeds and three broad distal lobes. CONCLUSIONS: Pararaucaria taquetrensis represents the oldest known Cheirolepidiaceae seed cones from the Southern Hemisphere, and this material highlights the importance of compression and impression fossils in understanding the distribution of fossil taxa. This material also suggests that Cheirolepidiaceae cone scales can be easily confused with those of another common conifer family, the Araucariaceae, which has important implications for accurately understanding Mesozoic conifer diversity and paleoecology.